Sanhua decoction: Current understanding of a traditional herbal recipe for stroke - Zheng, Lanlan; Meng, Linglei; Liang, Huazheng; Yang, Jiandao (Frontiers in Neuroscience, 2023)
Both thrombolytic and endovascular therapies are optimal treatment options for patients with acute ischemic stroke, but only less than half of these patients can benefit from these treatments. Traditional Chinese medicine has a long history in successfully managing ischemic stroke using both herbal and physical therapeutics. Among herbal recipes, Sanhua decoction (SHD) is one of the classical prescriptions for ischemic stroke. The present review aimed to summarize evidence from both clinical and basic research to demonstrate its efficacy in managing ischemic stroke and the potential mechanisms underlying its therapeutic effects, which will provide evidence on the therapeutic effect of this herbal recipe and guide future studies on this recipe. SHD is composed of four herbs, Rheum palmatum L. [Polygonaceae], Magnolia officinalis Rehder & E.H.Wilson [Magnoliaceae], Citrus × aurantium L. [Rutaceae], Hansenia weberbaueriana (Fedde ex H.Wolff) Pimenov & Kljuykov [Apiaceae]. We found that the majority of clinical studies on SHD are case reports and they showed positive therapeutic effect of SHD on both acute and chronic ischemic stroke. There are over 40 bioactive compounds identified in SHD, but few experimental studies have examined their individual molecular mechanisms. As an extract of SHD, it improves neurological functions through suppressing inflammation, protecting the blood brain barrier from degradation, restoring the number of neural stem cells, inhibiting apoptosis and brain edema, scavenging oxygen free radicals, and regulating the brain-gut axis. These will lay the theoretical foundation for future studies on this prescription and its clinical application. Future research may need to confirm its clinical efficacy in large-scale clinical trials and to disentangle its bioactive compounds and their potential mechanisms.